HE INFLUENCE OF ZAKAT, INFAQ, SADAQOH (ZIS) ON POVERTY ALLEVATION - RIDA RAHIM; TAFDIL HUSNI; RIYADI APRAYUDA; RIZKI FADHEL D (Maqdis: Jurnal Kajian Ekonomi Islam, 2020)
This study aims to analyse the influence of the amount of ZIS funds distributed to the community, unemployment and inflation rate, on poverty using economic growth as a moderating variable. The results showed that ZIS funds and economic Growth had a significant negative impact on the poverty rate. The moderating variable of economic growth was able to strengthen the relationship between the ZIS funds and the poverty rate. This study has a limitation as it only looked at the overall ZIS funds and the poverty rate in general. This study provides a perspective that the role of the ZIS funds distributed to the community is able to show its consistency and reduce the poverty rate. Thus, the ZIS funds can be considered as one of the main strategies to lessen the poverty rate.